Comparative Study of Lingual Papillae, Lingual Glands and Lyssa of the Tongue of Selected Wild Felids (Carnivora, Felidae) in Biological Aspects - Goździewska-Harłajczuk, Karolina; Barszcz, Karolina; Klećkowska-Nawrot, Joanna; Hamouzová, Pavla; Čížek, Petr; Kuropka, Piotr; Kvapil, Pavel (Biology, 2023)
Although much attention has been paid in the literature to the morphology of the tongue in various animal species, including some Felidae, it has not yet been described in detail in the vulnerable Neofelis nebulosa and Panthera leo bleyenberghi and the last concern Lynx lynx and Otocolobus manul. Therefore, the present study aimed to characterize the features of the tongue surface, lingual glands and lyssa in the above-mentioned four selected wild species of the Pantherinae and Felinae subfamilies. Macroscopic, histological, histochemical and ultrastructural analyzes were used in the present work. Comparative analyzes of the dorsal tongue surface showed the presence of mechanical lingual papillae on five subtypes of filiform papillae on the apex and body and conical papillae on the root of the tongue. Gustatory papillae in the four analyzed species were fungiform papillae and various numbers of vallate papillae. Foliate papillae were absent in P. leo bleyenberghi and L. lynx, while delicate smooth folds, which were separated by parallel grooves but without taste buds, were present in N. nebulosa. The vallate and foliate papillae were accompanied by lingual glands, which produced a serous secretion, whereas the mixed lingual glands of the lingual root were with a predominance of mucus secretions comparable to four captive Felidae species. In the median plane on the ventral surface of the apex under its epithelium and within the muscle fibers, the lyssa was also observed to a varying degree, with the least developed, and thought about the size of the entire tongue, was in P. leo bleyenberghi. The lyssa structure in the four species was dominated by adipose tissue. The obtained results contribute knowledge concerning the functional anatomy of the tongue in four selected Felidae species, especially in terms of comparative anatomy.
Keywords: Panthera leo bleyenberghi; tongue; hypercarnivorous diet; Neofelis nebulosa; Otocolobus manul; Lynx lynx